PROBLEMS OF IDENTIFYING SIGNS OF A VICTIM IN THE CRIMES DEPOTS PROVIDED BY ARTICLES397–400 OF THE CRIMINAL CODE OF UKRAINE - Куцевич , М. П. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2019)
Annotation. One of the key signs of so-called special structures of crimes, in article 397–400 of the Criminal Code of Ukraine of 05.04.2001 (next – CC), is an injured person. At present, a doctrinal approach to interpreting the content of signs of a victim in the warehouses of these crimes is distinguished by its inaccurate and discompliance with the literal meaning of the notions taken to indicate signs of such a victim in a special regulatory legislation. Therefore, it requires a Legal norms that would ensure the protection of such victim. The purpose of the article is to determine the main problems that arise when determining the signs of a victim in warehouses of crimes stipulated in article 397–400 of the Criminal Code and the ways of their solution. The study demonstrated the following problems: The concept of a defender and a representative who provides legal assistance, taken by the legislator, as such, indicating the special legal status of the participant in the relevant proceedings. In the warehouses of crimes stipulated in art. 397–400 of the Criminal Code, the integral characteristic of the special victim is: The defender, in connection with the activities associated with providing legal assistance Close relatives of the defender, in connection with the activities related to the provision of legal assistance to the defender The representative in connection with activities related to the provision of legal assistance to Close relatives of the representative in connection with the activities related to the provision of legal assistance to the representative. The term «representative, in connection with activities related to legal assistance,» is not covered by a number of participants in procedural proceedings called the representative, but not formally are those that provide legal assistance. Outside the criminal law guard, which is provided by a group of special norms, which are located in section XVIII of the special part of the Criminal Code of Ukraine «Crimes against justice»: Art. 397–400 of the Criminal Code, five types of procedural proceedings that Effectively protect and represent the interests of another participant of procedural proceedings, but formally their procedural activity has a different name: Representative of the victim, legal entity, namely: Supervisor, other person, authorized by law or constituent documents, employee of legal entity by proxy – Part 2 of article 58 of the CPC; Legal representative of the minor victim-article 59 of the Criminal Procedural Code; Witnesses ’ advocate – Article 66 of the Criminal Procedural Code; Legal representative of a participant in the case-P. 1 of art. 58 Commercial Procedural Code, 1 of art. 58 Civil Procedural Code, Part 1 of art. 57 Code of Administrative Justice; A legitimate representative of a person brought to administrative responsibility, and a victim who is underage or persons who, because of his physical or mental disabilities, may not exercise their rights in cases of administrative offences. The case about an administrative offense-article 270 Code of Administrative Justice. In order to build an effective system of special criminal and legal protection of the participants of procedural proceedings, which actually carry out the function of representation of interests, rights and duties of other participants of procedural proceedings, appropriate amendments to article 397– 400 of the Criminal Code are required.

Анотація. Однією з ключових ознак так званих спеціальних складів злочинів, передбачених у ст.ст.397–400 Кримінального кодексу України від 05.04.2001 (далі – КК), є потерпілий. На сьогодні доктринальний підхід до тлумачення змісту ознак потерпілого у складах вказаних злочинів вирізняється своєю неточністю і невідповідністю буквальному змісту понять, ужитих на позначення ознак такого потерпілого в спеціальному регулятивному законодавстві. Тому потрібне глибоке наукове переосмислення змісту системи спеціальних кримінально-правових норм, які б забезпечували охорону такого потерпілого. Мета статті полягає у визначенні основних проблем, які виникають при визначенні ознак потерпілого у складах злочинів, передбачених ст.ст.397–400 КК, та шляхів їх вирішення. Проведене дослідження продемонструвало такі проблеми: Поняття «захисник» та «представник, який надає правову допомогу», вжиті законодавцем як такі, що позначають спеціальний правовий статус учасника відповідного провадження. У складах злочинів, передбачених в ст.ст. 397–400 КК, цілісна характеристика спеціального потерпілого така: захисник у зв’язку з діяльністю, пов’язаною з наданням правової допомоги; близькі родичі захисника у зв’язку з діяльністю, пов’язаною з наданням правової допомоги захисником; представник у зв’язку з діяльністю, пов’язаною з наданням правової допомоги; близькі родичі представник, у зв’язку з діяльністю, пов’язаною з наданням правової допомоги представником. Поняттям «представник у зв’язку з діяльністю, пов’язаною з наданням правової допомоги» не охоплюються учасники процесуального провадження, які називаються представником, однак формально не є такими, які надають правову допомогу. За межами кримінально-правової охорони, що забезпечується групою спеціальних норм, розташованих у розділі XVIII Особливої частини КК України «Злочини проти правосуддя», а саме ст.ст. 397–400 КК, залишаються п’ять видів учасників процесуального провадження, які здійснюють фактично захист і представництво інтересів іншого учасника процесуального провадження, однак формально їх процесуальна діяльність має іншу назву: представник потерпілого, юридичної особи, а саме: керівник, інша особа, уповнова- жена законом або установчими документами, працівник юридичної особи за довіреністю – ч. 2 ст. 58 КПК; законний представник неповнолітнього потерпілого – ст. 59 КПК; адвокат свідка – ст. 66 КПК; законний представник учасника справи – ч. 1 ст. 58 ГПК, ч. 1 ст. 58 ЦПК, ч. 1 ст. 57 КАС; законний представник особи, яка притягається до адміністративної відповідальності, і потерпілого, які є неповнолітніми або особами, що через свої фізичні або психічні вади не можуть самі здійснювати свої права у справах про адміністративні правопорушення – ст. 270 КУпАП. З метою побудови ефективної системи спеціальної кримінально-правової охорони учасників процесуальних проваджень, які фактично здійснюють функцію представництва інтересів, права та обов’язків інших учасників процесуальних проваджень, необхідні відповідні зміни до ст.ст.397–400 КК.
ПРОБЛЕМИ ВИЗНАЧЕННЯ ОЗНАК ПОТЕРПІЛОГО В СКЛАДАХ ЗЛОЧИНІВ, ПЕРЕДБАЧЕНИХ СТАТТЯМИ 397–400 КК УКРАЇНИ
Keywords: defender; representative; participant of procedural proceeding which provides representation (protection) of rights and interests of another participant of procedural proceeding.; захисник; представник; учасник процесуального провадження; який здійснює представництво (захист) прав та інтересів іншого учасника процесуального провадження.